Multinodular goiter: an unusual case presentation - Kunal, Abhishek; Bhadaranavar, Shreyas; Dhaigude, Balaji; Bharadwaj, Ramachandra (International Journal of Research in Medical Sciences, 2017)
Goitrous enlargement of the thyroid gland usually presents as a nontender anterior neck mass. Asymptomatic patients may be treated medically, which often reduces the size of the gland or avoids progression of the disease. Neglected or ineffectively treated cases may grow beyond the confines of the gland, which primarily occurs caudally into the mediastinum. In this paper, we present a patient with multinodular goiter with a large retrosternal component.